The Diversity of Fish in The Aek Sibundong District Dolok Sanggul Regency Humbang Hasundutan - Hesty Wahyuningsih (International Journal of Ecophysiology, 2021)
The diversity of fishes in Aek Sibundong, Dolok Sanggul regency, Humbang Hasundutan district, was conducted from April to October2018. The aim of this research was to analyze variety of fishes and their physical-chemical factors related to fishesin Aek Sibundong. This research used purposive sampling method on four location based on human activities. The first location was stationed with no activities, the second location tofu waste disposal station, the third location was slaughter house station and last location was belonge to sand dredging station. Sampling used nets as trap for the fishes. Seven species of fishes had been found from the sites where classified into 3 order ( spesies from ordo Cypriniformes 4, Perciformes 1 and Siluriformes 2). The result showed that station 1 had the highest fish density was 0,59 ind/m2 belong to Tor tambroides and the highest fish diversity index at 1,318. The temperature, light intensity, light penetration, phosphate, and Biochemical Oxygen Demand (BOD5) had strongly correlated with fish diversity in the waters of the Aek Sibundong.